Effect of Cr\(^{3+}\) Concentration and Heat-treating Temperature on Structural Property of Cr\(^{3+}\)- doped TiO\(_2\) Nanowires Synthesized by Hydrothermal Method - Loan, Trinh Thi; Long, Nguyen Ngoc (Communications in Physics, 2015)
Anatase Ti1-xCrxO2 nanowires with Cr3+ dopant contents ranging from x = 0 to 0.1 have been successfully synthesized by hydrothermal method. The nanowires were prepared from anatase titanium dioxide powder (TiO2), chrome nitrate (Cr(NO3)3), and sodium hydroxide (NaOH). The effect of the Cr3+ concentration and heat-treating temperature on structure, morphology of the synthesized Ti1-xCrxO2 samples has been studied by X-ray diffraction, scanning electron microscopy and Raman scattering. At low heat-treating temperature (≤ 600 oC), the samples exhibited anatase phase and in the Raman spectra of samples with x ≥ 0.01 exhibited a new series peak at 120, 236, 250, 292, 362, 430, 467 and 550 cm-1, which were assigned to the localized vibrational modes related to the complexes containing Cr3+ ion. But at high heat-treating temperature (1100 oC), the samples exhibited rutile phase, in the Raman spectra the above-mentioned peak series did not appear, instead of this, only observed shifting and broadening of characteristic Raman modes (Eg and M) for rutile TiO2 with increasing Cr3+ dopant content, which proves that the Cr3+ ions have replaced the Ti4+ ions in the rutile TiO2 host lattice. The lattice constants of both the rutile and anatase TiO2 crystallites have been hardly affected by Cr3+ ions dopant contents.